Pre-planting application of soil sterilents and herbicides for management of crown gall disease on Tolt’ cherry rootstock - GUPTA, A K; KAMAL, B (The Indian Journal of Agricultural Sciences, 2011)
Field experiments were collductcd during 2002 and 2003 at Nauni, Solan to find out the effect of pre-planting application of different soil sterilcnts and herbicides oil thc incidence of crown gall caused by Agrobncterium tumefacines on ’Colt’ cherry rootstock. Application of formaldehyde (4 %) resulted in minimum incidence of crown gall (9.77 %) compared with tile control (53.25 %) on ’Colt’ cherry rootstock. Application of different soil sterilizing agents resulted in decline of non- target microbial population of fungi, bactcria and actinomycetes initially but its population increascd in subsequent montlls. Oxyfluorfcn (0.5 litrei ha) also reduced thc incidence (30.33 %) compared with the control (60.62 %). Mechanical weeding as not found effective in reducing the crown gall incidence.